A model for knickpoint migration in first‐ and second‐order streams. Issue 14 (23rd July 2014) - Bressan, Filippo; Papanicolaou, A. N.; Abban, Benjamin
Abstract We introduce a new theoretical framework for knickpoint migration in unventilated flows prevalent in channelized semicohesive first‐ and second‐order streams characterized by a sequence of constrictions and expansions in the channel cross section. A key feature of the framework is the inclusion of shear‐induced fluvial erosion due to flow suction at the nappe as the key mechanism driving migration. Channel surveys, water stage, time‐lapse photography, and laser scans from Mud Creek, Iowa, USA, confirm this unventilated erosive mechanism and reveal a dual advective‐diffusive mode of retreat. We treat the fluvial bed shear stress as being similar to the flow on the lee side of a submerged obstacle and derive a governing equation which is a generalized Burgers' equation. The equation is solved to successfully simulate knickpoints monitored in two sites (Iowa and Mississippi), and a modified Peclet number is used to analyze the advective‐diffusive nature of the knickpoint migration.